Evaluation of dose calculations on different CBCT-based synthetic-CTs: a comparative study - Colombo, Lorenzo; Oumani, Ayoub; Delassales, Edouard; Uluer, Melih; Aydin, Gokhan; Teboul, Olivier; Paragios, Nikos; Gungor, Gorkem (ELSEVIER IRELAND LTD, 2024)
Annual Meeting of the European-Society-for-Radiotherapy-and-Oncology (ESTRO), Glasgow, ENGLAND, MAY 03-07, 2024
Keywords: Adaptive; synthetic\\-CT from CBCT; Dose calculation